مقارنة الأداء المالي للبنوك التقليدية والإسلامية في المملكة العربية السعودية - علوي أبوبكر أحمد بلفقيه
The 2009-2018 period witnessed many political and economic changes in the world and the Arab Gulf in general, and in the Kingdom of Saudi Arabia in particular. These changes may affect the performance of the banking sector and threaten the growth and continuity of banks. Due to the different bases of business between Islamic and conventional banks, this study will examine the performance of Islamic and conventional banks in the Kingdom of Saudi Arabia from 2009 to 2018. The study will also suggest the necessary recommendations to address the weaknesses and deficiencies related to the performance of these banks. The study sample comprises all 12 Saudi national banks (8 conventional banks and 4 Islamic banks). The study relies on the indicators of liquidity (cash balance ratio), profitability (return on average equity and return on average assets), activity (percentage of resource investment and investmentdeposit ratio), and financial solvency. The differences between the means of the financial ratios of conventional banks and Islamic banks will be measured using descriptive analysis (mean and standard deviation) and inferential analysis (t-test and Levene’s test). Data analysis will be carried out using the Statistical Analysis Program (SPSS). The findings have shown that Islamic banks have high liquidity compared to conventional banks. Profitability indicators showed that there are no differences between conventional banks and Islamic banks on the use of their own resources to achieve profits in the average of study period. Both types of banks had close efficiency in using assets to achieve profits. In addition, the activity indicators showed that the conventional banks employ their resources better than Islamic banks, while both types of banks are approximately similar in investment-deposit ratio. Moreover, both conventional banks and Islamic banks have an acceptable solvency. The study concluded with a set of recommendations including that Islamic banks must beware that the liquidity does not reach the level of excess liquidity. Islamic banks must work towards increasing cooperation, coordination, and integration between banks at the local and international levels, as well as develop an Islamic financial market and innovate Islamic financial tools. In addition, it is recommended for Islamic banks to amalgamate to form an ideal size of an Islamic bank to be a role model. More attention must be given to developing and improving Islamic banks system and introducing new and diversified investment methods. Finally, it is recommended to establish training institutions to educate bank employees and consequently avoid a shortage of experts in the field of banking in the future.